2013
DOI: 10.1371/journal.pone.0058124
|View full text |Cite
|
Sign up to set email alerts
|

PspA Family Distribution, Antimicrobial Resistance and Serotype of Streptococcus pneumoniae Isolated from Upper Respiratory Tract Infections in Japan

Abstract: BackgroundThe protection against pneumococcal infections provided by currently available pneumococcal polysaccharide conjugate vaccines are restricted to the limited number of the serotypes included in the vaccine. In the present study, we evaluated the distribution of the pneumococcal capsular type and surface protein A (PspA) family of pneumococcal isolates from upper respiratory tract infections in Japan.MethodsA total of 251 S. pneumoniae isolates from patients seeking treatment for upper respiratory tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…This is largely akin to our previous findings for isolates from patients suffering from CAP [14] as well as data from other countries in Europe [26] and the Far East [27,28]. Thus, determination of the prevalent STs/SGs in patients may help in fine-tuning therapy by avoiding the use of antibiotics known to be poorly effective.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is largely akin to our previous findings for isolates from patients suffering from CAP [14] as well as data from other countries in Europe [26] and the Far East [27,28]. Thus, determination of the prevalent STs/SGs in patients may help in fine-tuning therapy by avoiding the use of antibiotics known to be poorly effective.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, determination of the prevalent STs/SGs in patients may help in fine-tuning therapy by avoiding the use of antibiotics known to be poorly effective. Determination of the nucleotide sequence of the ␣-helical region of the pneumococcal surface protein (PspA), also proposed as a predictor of multiresistance [28], could not be examined in the context of the present study.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, vaccination with Pneumovax 23, a pneumococcal polysaccharide-based vaccine without a carrier protein, only protects about 39% to 41% of adults against secondary bacterial infection [10,11]. Recent efforts have been directed towards using pneumococcal surface protein A (PspA) as a vaccine candidate since it is highly conserved among the >90 serotypes [12,13]. PspA is classified into three families that consist of six clades [14].…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have looked at pspA frequencies (54)(55)(56)(57)(58), those studies were focused on pre-PCV7 strains, which are no longer representative of the serotypes currently isolated in the United States, or strains from nonpediatric populations (49). In a recent report, we showed that IPD strains collected in Alabama from 2002 to 2010 were of pspA family 1 or family 2 in 96% of cases (6).…”
Section: Discussionmentioning
confidence: 99%